EVALUASI FAKTOR-FAKTOR YANG MEMPENGARUHI QUALITY OF WORK LIFE (Studi Kasus PT. Pelabuhan Indonesia II Persero) - Anisah Anisah (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
This study aims to evaluate the factors that affect the Quality of Work Life at Port PT Indonesia II (persero), and this research is quantitative research is an investigation about the social issues based on testing a theory consists of a variable-variables, measured by numbers, and analyzed with the statistics procedures to determine whether predictive generalizations of these theories is correct. the data used in this research is qualitative data by spreading the questionnaire covered alternative answer had been provided to the respondent, hereinafter the qualitative data in the quantitative method using Likert Summated Rating with a given score. After the data is collected then analyzed using factor analysis. From all this research analysis to see that there are six variables that influence positively and significantly to Quality of Work Life and the rest have not been significant then it can be said that the influence factors towards the Quality of Work Life at Port PT Indonesia II (Persero)Keywords : Quality of Work Life